From Setback to Growth: A Phenomenological Study of Psychometrician Exam Retakers - Janrico David C. Basa; Irish Joy J. Gonzales; Rio Haina R. Malibong; Chester Alan R. Merza (Philippine Social Science Journal, 2024)
Licensure examinations serve as a critical gateway to professional practice, often creating significant stress and challenging experiences for those who fail and must retake them. This study explored how the experience of failing and retaking the psychometrician licensure examination impacted the self-concept of seven examinees from Region 1, Philippines. Using interpretative phenomenological analysis of online interviews, the research revealed that retaking the exam had profound and varied effects on their self-perception, ranging from restoring confidence to completely transforming their sense of self. This research highlights the often-overlooked experiences of licensure exam retakers and contributes to understanding the psychological impact of setbacks and perseverance on the path to success. By focusing on the lived experiences of these individuals, the study offers valuable insights into the challenges and triumphs faced by those striving to achieve professional licensure.